Persepsi Petani Terhadap Penggunaan Benih Padi Inpago di Kecamatan Burneh Kabupaten Bangkalan (Jurnal Agribisnis Indonesia, 2025)
Inpago rice seed is suitable for planting in dryland conditions, such as Bangkalan Regency. This seed could tolerate dry weather or climatic conditions. However, this seed is not the seed choice currently used by farmers in Burneh District. The purpose of this study is to explore farmers’s level of satisfaction with the use of Inpago rice seeds and to find out how they perceive the use of Inpago rice seeds in Burneh District. The sample-used was 43 respondents using a simple random sampling. Data analysis uses the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The research showed that the farmer satisfaction index value was 87.51%, meaning that farmers' satisfaction with the attributes of Inpago rice seeds was classified as very satisfied, with an average conformity level of 97.00%, shows that farmers have a positive perception of Inpago rice seeds. Advice that can be recommended to farmers to meet satisfaction is to pay attention to the age of the seedlings before transplanting. After harvesting, the quality of grain and rice can be evaluated based on attributes such as color, size, aroma, and texture to meet farmers' expectations.